A minimal model for solvent evaporation and absorption in thin films - Hennessy, M; Ferretti, G; Cabral, J; Matar, O (Elsevier, 2016)
We present a minimal model of solvent evaporation and absorption in thin films consisting of a volatile solvent and non-volatile solutes. An asymptotic analysis yields expressions that facilitate the extraction of physically significant model parameters from experimental data, namely the mass transfer coefficient and composition-dependent diffusivity. The model can be used to predict the dynamics of drying and film formation, as well as sorption/desorption, over a wide range of experimental conditions. A state diagram is used to understand the experimental conditions that lead to the formation of a solute-rich layer, or "skin", at the evaporating surface during drying. In the case of solvent absorption, the model captures the existence of a saturation front that propagates from the film surface towards the substrate. The theoretical results are found to be in excellent agreement with data produced from dynamic vapour sorption experiments of ternary mixtures comprising an aluminium salt, glycerol, and water. Moreover, the model should be generally applicable to a variety of practical contexts, from paints and coatings, to personal care, packaging, and electronics.